ALLELOPATHY EFFECT OF Ageratum conyzoides LEAVES AND Imperata cylindrica ROOTS ON SEED GERMINATION AND PLANT GROWTH OF MUNG BEANS - Utari, Nofi; Anisah, Siti Nur; Krisdianto, Krisdianto; Sulistijorini, Sulistijorini (Program Studi Agroteknologi Universitas Siliwangi, 2025)
Ageratum conyzoides, and Imperata cylindrica are cosmopolite weeds in agricultural land that can reduce the productivity of cultivated plants. This study aims to analyze the effect of A. conyzoides leaves biomass and I. cylindrical former plant media on the percentage of germination and growth of mung beans (Vigna radiata). The research was conducted by making 3 (three) replications of each Treatment. Treatment A (application of A. conyzoides leaf biomass to the planting media), Treatment B (used I. cylindrica planting media), and Control Treatment. Anova test and Tukey HSD test were conducted using R-Studio. The results showed that Treatments (A) and (B) reduced the success of mung bean germination compared to the control (97%), with A at 60% and B at 50%. The changes in leaf number and root length are very noticeable compared to plant height. The allelopathic effect was stronger in A than B. Biomass of A. conyzoides and used media of I. cylindrica has the potential to inhibit germination and early growth of mung beans.